2023
DOI: 10.7759/cureus.33756
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge, Attitude, and Practice Toward Vitamin D Deficiency in Al-Qunfudhah Governorate, Saudi Arabia

Abstract: Background: Vitamin D is a very important component of all vital functions in the human body. Its deficiency is a major public health issue worldwide and is associated with a broad spectrum of diseases. This study assessed knowledge, attitude, and practices regarding vitamin D deficiency among the general population in the Al-Qunfudhah governorate, Saudi Arabia.Methods: An analytical cross-sectional study was carried out among the population in Al-Qunfudhah governorate, Saudi Arabia. A self-administrated onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…[27][28][29] Female gender, receiving medical information from physicians and being unmarried, young and highly educated were recently reported as determinants for good VD knowledge. 26 The current study reported a significant improvement in the students' practices following the intervention (p < 0.001). The percentage of students who applied satisfactory practices had been only 4.8% before the awareness programme but increased to 48.2% after it.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…[27][28][29] Female gender, receiving medical information from physicians and being unmarried, young and highly educated were recently reported as determinants for good VD knowledge. 26 The current study reported a significant improvement in the students' practices following the intervention (p < 0.001). The percentage of students who applied satisfactory practices had been only 4.8% before the awareness programme but increased to 48.2% after it.…”
Section: Discussionmentioning
confidence: 48%
“…The study reported good attitude of female to preventing VD deficiency and this could encourage them to change their behaviour. 26 A low level of knowledge and awareness regarding VD deficiency has been reported worldwide, and this is likely to be a factor contributing to global VD deficiency. [27][28][29] Female gender, receiving medical information from physicians and being unmarried, young and highly educated were recently reported as determinants for good VD knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations